Exploring Sustainable Approaches: Efficacy of Plant-Based Oils and Beauveria bassiana Fungal Spores in Managing Silverleaf Whitefly (Bemisia tabaci) Infestations: Managing Silverleaf Whitefly (Bemisia tabaci) Infestations - kurnianto, agung sih; Purnomo, Hari; Sucipto , Irwanto; Muhlison , Wildan; Dewi, Nilasari; Kamalin, Indah M.; Khoiruttamam, Muhammad Zulfa; Aini, Wilda Qurrotul; Magvira , Nur Laila; Handoko, Rose Novita Sari (Journal of Tropical Life Science, 2025)
The Silverleaf whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), is a destructive insect pest of important greenhouse and field crops. Several studies have shown the effectiveness of Beauveria bassiana in controlling Silverleaf whitefly.. However, a major challenge lies in the rapid evaporation of water in greenhouse crop models. Therefore, this study aimed to evaluate the effectiveness of B. bassiana against the whitefly and test its compatibility with various vegetable oils as carrier media. This research at the Agrotechnology Laboratory, Faculty of Agriculture, University of Jember, used pure isolates of B. bassiana for mass production until conidia reached 2.5 x 107 per gram. We employed a Completely Randomized Design (CRD) with factors of vegetable oil (Corn Oil, Vegetable Oil, Soybean Oil) and concentration (5%, 10%, 15%) using Ultra Low Volume (ULV) formulations. The results revealed that the addition of vegetable oils enhanced the effectiveness of B. bassiana in controlling Silverleaf whitefly, with corn oil having the most significant impact due to its high carbohydrate content that supported B. bassiana viability. Additionally, the concentration of B. bassiana formulation also influenced the rate of whitefly mortality (mycocity), with a 15% concentration yielding the best results. Whitefly nymphs infected with B. bassiana exhibited slowed activity and reduced appetite. Adding vegetable oil facilitated the formation of a protective biofilm around conidia, shielding them from UV radiation, increasing conidia viability, and supporting field application. The infection process by B. bassiana required 6 days to achieve 100% mortality. This research suggests that B. bassiana can be an effective alternative for controlling Silverleaf whiteflies, especially when used with plant-based oils as a carrier medium. This approach may help reduce reliance on chemical pesticides and address issues related to Silverleaf whitefly resistance to insecticides.